2019
DOI: 10.1016/j.trsl.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment of renal fibrosis by magnetic resonance imaging and ultrasound techniques

Abstract: Renal fibrosis is a useful biomarker for diagnosis and guidance of therapeutic interventions of chronic kidney disease (CKD), a worldwide disease that affects more than 10% of the population and is one of the major causes of death. Currently, tissue biopsy is the gold standard for assessment of renal fibrosis. However, it is invasive, and prone to sampling error and observer variability, and may also result in complications. Recent advances in diagnostic imaging techniques, including magnetic resonance imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 184 publications
(179 reference statements)
1
82
0
Order By: Relevance
“…A multiparametric MRI approach has the unique potential to identify changes in renal tissue structure, perfusion, and oxygen consumption that occur in parallel in renal fibrosis. 9,10 Previous validation studies showed the association of MRI parameters with renal allograft dysfunction and histopathology, 4,6,7,[9][10][11] with few studies focusing on comparisons of diagnostic performance among techniques 7,12 or the prediction of allograft outcome. Our preliminary study identified cortical ADC and T 1 as the parameters with the best diagnostic performance for chronic allograft dysfunction, association to histopathology, renal function decline, and graft survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multiparametric MRI approach has the unique potential to identify changes in renal tissue structure, perfusion, and oxygen consumption that occur in parallel in renal fibrosis. 9,10 Previous validation studies showed the association of MRI parameters with renal allograft dysfunction and histopathology, 4,6,7,[9][10][11] with few studies focusing on comparisons of diagnostic performance among techniques 7,12 or the prediction of allograft outcome. Our preliminary study identified cortical ADC and T 1 as the parameters with the best diagnostic performance for chronic allograft dysfunction, association to histopathology, renal function decline, and graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…We did not include emerging MRI modalities with utility in renal fibrosis, such as magnetization transfer imaging (MTR) or MR elastography. 10 MR elastography data were acquired, and detailed analysis will be presented in a separate paper.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, renal revascularization seems to be effective in selective cohorts of patients with RVD, such as those with low levels of albuminuria 13 . Renal fibrosis is also considered to be an important biomarker, determinant of renal outcomes, and a therapeutic target in CKD 9 , which can predict outcomes in renal transplant recipients and native kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the b-values were collected during separate acquisitions, which may lead to some motion or misregistration artifacts. Newer DWI methods allow for acquisition of multiple b-values during a single acquisition period 9 . However, we excluded most b-values less than 300 s/mm 2 to minimize the effects of renal perfusion on ADC.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation